Nutraceuticals and functional foods for the control of plasma cholesterol levels. An intersociety position paper. (August 2018) - Poli, Andrea; Barbagallo, Carlo M.; Cicero, Arrigo F.G.; Corsini, Alberto; Manzato, Enzo; Trimarco, Bruno; Bernini, Franco; Visioli, Francesco; Bianchi, Alfio; Canzone, Giuseppe; Crescini, Claudio; de Kreutzenberg, Saula; et al.
Abstract: Current evidence shows that cholesterol management either reduces the likelihood of cardiovascular disease (CVD) or slows down its progression. Hence, it is important that all health professionals make appropriate use of all the available intervention strategies to control risk factors: from dietary improvement and positive lifestyle changes to the use of functional foods, food supplements, and drugs. This review examines the effect of the most frequently occurring cholesterol-lowering substances in functional foods or in supplements across Europe, namely plant sterols and stanols, monacolin K found in red yeast rice, berberine and beta-glucans. We conclude that currently available supplements and functional foods can effectively reduce plasma LDL cholesterol levels by about 5 to 25%, either alone or in combination. Suitable candidates for these products are mainly individuals at low absolute cardiovascular risk at a young age or according to classic algorithms. Of note, despite being freely available for purchase, these products should be used following shared agreement between the physician and the patient ("concordance").